2019
DOI: 10.18549/pharmpract.2019.4.1613
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with quality of life among community pharmacists in Lebanon: results of a cross-sectional study

Abstract: Objective:The objective of this study was to assess the quality of life and the factors associated with it among community pharmacists in Lebanon.Methods:This cross-sectional study was carried out between March and July 2018, enrolling 435 pharmacists, using a proportionate random sample of community pharmacies from all districts of Lebanon. The validated Arabic translation of the Short-Form 12 (SF12v2) was used to derive 2 summary scores: physical and mental component summaries (PCS and MCS).Results:Lebanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…An online software was used to randomly select the community pharmacies sample using the list of pharmacies provided by the Lebanese Order of Pharmacists (OPL). Similar methodology was used in previous papers [22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: General Study Designmentioning
confidence: 94%
“…A study conducted between 435 pharmacists from Lebanon found a significant association between higher stress and lower mental QOL. 45 At the pharmacy student level, two studies found a significant association between stress and QOL. The first, conducted in the United States among 109 Pharm.D.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in 2018 among 435 Lebanese pharmacists, and it found that higher stress has a significant influence on lower mental QOL. 45 Another study conducted among 109 doctor of pharmacy students in the United States found a negative correlation between stress and mental QOL. 46 Likewise, a study conducted among 110 pharmacy students in Ghana found a significant correlation between stress and QOL from the middle until the end of the semester.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an assessment of the societal perspective showed that the general population is barely satisfied with pharmacists' services (Iskandar et al, 2017). Other studies reported lower empathy (Hobeika, Hallit, et al, 2020), burnout (Rahme et al, 2020), and low quality of life (Sacre, Obeid, et al, 2019) among pharmacists.…”
Section: Dg15[p]-mentioning
confidence: 99%
“…Pharmacy practice in Lebanon faces economic and financial difficulties (despite small breakthroughs in this regard), reflecting the Lebanese context and leading to pharmacists' dissatisfaction (Hallit, Zeenny, Sili, & Salameh, 2017), burnout (Rahme et al, 2020), lower empathy towards patients (Hobeika, Hallit, et al, 2020), and reduced quality of life (Sacre, Obeid, et al, 2019), all expected to lower service quality and decrease professional sustainability on the long run.…”
Section: Dg21[p]-mentioning
confidence: 99%